Design of internet of things-integrated programmable logic controller for demonstrating automated sorting systems - Intawong, Narit; Saengchandr, Banjerd; Inkamchuer, Manit; Thongprom, Morakot; Sukontanakarn, Viroch (Bulletin of Electrical Engineering and Informatics, 2025)
This project presents an automated workpiece sorting demonstration system controlled by a programmable logic controller (PLC) and a touch screen interface. The system integrates an internet of things (IoT) gateway that communicates with the PLC via Modbus remote terminal unit (RTU) over RS-485, allowing the transfer of digital data. This data is processed using JavaScript within the Node-RED platform to manage machine operations and display the operational status. The system supports both manual control and IoT-based management, enabling the sorting of cylindrical workpieces to designated areas. Metal and non-metal detection is achieved using capacitive and inductive sensors, respectively, which inform a stepper motor to manipulate the workpieces via a gripper pneumatic to the specified locations. Test results indicate a high detection capability of the sensors: the capacitive sensors achieved a 95% detection rate over 100 trials, while the inductive sensors recorded a 97% detection rate. Furthermore, the precision of placing workpieces at the target locations was 92% across 100 attempts. This system showcases an effective combination of automation and IoT technologies, improving efficiency in workpiece sorting processes.